Portal untuk orang pekak: Ruangan forum, informasi, berita dan pekerjaan / Normaliza Latip - Normaliza, Latip (2003)
The portal for the deaf is mainly built for the deaf community in Malaysia. @pekak.com is one of the deaf portals in Bahasa Melayu, that serves all the needs required in their daily lives. it is a platform for exchanging and retrieving information between users, virtually. The portal provides several services for users such as chat rooms and forums, which enable them to interact with normal users without communication barriers, and search engines that allow them to retrieve the information they need by just typing in the keyword. The project started off by having discussions and early schemes between the developers and supervisor. The literal review was then held to enhance the developers understanding in the build-up process, by examining similar portals that are available on the Internet, and collecting all the information needed. In the analysis phase, developers searched techniques, suitable software and schemes techniques that were useful to enhance the portal. The portal then went through designing phase, where program design, database design and user interface designs, were designed and born. After all of these phases ended, the next phase was programming, which was quite complicated to carry out by the developers. After that, the testing phase were held to test the efficiency of the portal and to make sure that it fulfils all of the objectives the developers want to accomplish. With the development of this portal, it is hoped that it can help the deaf community in information sharing and provide all the convenience that is suitable for the use of the deaf to carry out a normal life like other normal people.